Consumers Attitude Towards Location-Based Advertising: An Exploratory Study - Gana, Matthew A; Thomas, Toney K (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
A location-based service application is a recent innovative mobile application to travel industry. The adoption and use of this application by the consumers’ raised concerns on permission-based information to divulge. This study examined location-based advertising, a new and innovative location-based mobile marketing strategy available to business. The study conducted an interview using a focus group. It found that consumers attitude towards location-based advertising still an issue due to permission-based authority. The implications for the study and future research were discussed. The paper is structured into an introduction, literature, discussion, and conclusion.